Pengaruh Pengembangan Diri Terhadap Kualitas Mengajar Guru Pendidikan Anak Usia Dini - Nuryanti, Tri; Abdullah, Ghufron; Murniati, Ngurah Ayu Nyoman (Journal Prakarsa Paedagogia, 2022)
The purpose of this study was to: Analyze the effect of self-development on the quality of teaching early childhood education teachers in Ambarawa District, Semarang Regency. The population in this study were teachers of Early Childhood Education in Ambarawa District, Semarang Regency, amounting to 176 people, with a sample of 122 people using proportional random samples. The method used for data collection is a questionnaire method. The data analysis used is prerequisite test and hypothesis testing which includes multiple linear regression analysis to determine the effect of self-development and teacher's teaching experience on teaching quality. Data analysis used IBM SPSS Statistics 23. The results showed that self-development had a positive and significant effect on the teaching quality of PAUD teachers in Ambarawa District, Semarang Regency with a significance value of self-development variable of 0.012 (smaller than 0.05) and a regression coefficient of 0.226 (positive).